Tindak Pidana Pencurian Dengan Pemberatan (Studi Pada Putusan Nomor 398/Pid.B/2022/PN.Amb) - Paul Edward Mataheru; Yanti Amelia Lewerissa; Steven Makaruku (PATTIMURA Law Study Review, 2023)
The element of joint theft is defined as an act committed jointly, with the same intention as stipulated in Article 56 of the Criminal Code, namely participation in the act. Participation in committing is defined as "Committing together". In this context, of course, the perpetrators must be at least two people who commit the crime and who participate in the crime. This research uses normative juridical research methods with legal materials used, namely primary legal materials, secondary legal materials, and tertiary legal materials, data collection techniques are carried out through literature study and analyzed using qualitative analysis methods to answer the problems in this writing. Based on Decision No. 398/Pid.B/2022/PN.Amb, the author concludes that the judge could have implemented Article 55 of the Criminal Code because the actions committed by the defendant were also included in the crime of participation (Medepleger). The author concludes that it would be very fair if the judge sentenced the defendant to Article 363 paragraph (1) 4th jo Article 55 of the Criminal Code. The author also concludes that the defendant has previously been convicted, the sentence should have been aggravated not only for 2 years, because the defendant's actions fall into the category of qualifying or certain crimes and the threat of punishment is also aggravated where the main elements of theft are the same as the elements of theft in Article 362 of the Criminal Code, while the special elements that aggravate the punishment are contained in many elements, for example in paragraph (4) of Article 363 which consists of several alternatives, namely the aggravation of the object element, which lies at the time or incident when the theft is committed; and the perpetrators are more than one (with allies).